The Plasmid-Borne tet(A) Gene Is an Important Factor Causing Tigecycline Resistance in ST11 Carbapenem-Resistant Klebsiella pneumoniae Under Selective Pressure - Xu, Juan; Zhu, Zhongliang; Chen, Yanmin; Wang, Weizhong; He, Fang (Frontiers in Microbiology, 2021)
The emergence and prevalence of tigecycline-resistant Klebsiella pneumoniae have seriously compromised the effectiveness of antimicrobial agents in the treatment of infections. To explore the role of the plasmid-borne tet(A) gene in tigecycline resistance in carbapenem-resistant K. pneumoniae (CRKP), a total of 63 CRKP isolates were collected from a tertiary hospital in Hangzhou, China. The minimum inhibitory concentration (MIC) of tigecycline, mutation rate of tet(A) gene, genetic surroundings of tet(A)-carrying transmissible plasmid and the contribution of tet(A) mutation to tigecycline resistance were analyzed using antimicrobial susceptibility test, whole-genome sequencing, tigecycline resistance evolution experiment and plasmid conjugation experiment. Our results showed that 52.4% (33 isolates) of the test isolates carried the tet(A) gene; among them, 75.8% (25 isolates) exhibited a tigecycline non-susceptible phenotype (MIC = 4 mg/L). Three clonal groups (cluster I, cluster II and cluster III) were identified in these tet(A)-bearing isolates. All 17 isolates belonged to serotype KL21 (cluster I), which differed by only 13 SNPs, suggesting a clonal spread of tet(A)-positive ST11 K. pneumoniae with serotype KL21 occurred in the sampling hospital. The induction of tigecycline resistance experiments showed that 71.4% of strains evolved tet(A) mutations and developed a high-level tigecycline resistance. Eight amino acid substitutions were identified in these mutants. The most common amino acid substitution was A370V, followed by S251A and G300E. Twelve isolates carrying tet(A) mutants succeeded in the filter mating experiment with a conjugation efficiency of 10−3 to 10−8. Tigecycline MICs in E. coli EC600 transconjugants with a mutated tet(A) were 2-8-fold higher than those in E. coli EC600 transconjugants with a wild-type tet(A). One ColRNAI/IncFII type and two IncFII type tet(A)-bearing conjugative plasmids were identified in this study, including a class 1 integron containing multiple antibiotic resistance genes, i.e. tet(A), qnrS1, blaLAP-2, catA2, sul2 and dfrA14. Our study revealed the wide-spread situation of plasmid-borne tet(A) gene in clinical CRKP, and mutation of tet(A) is a potential driven force that lead to tigecycline resistance.